Sistema de tratamento híbrido utilizado na remoção do corante reativo 5g de um efluente têxtil sintético - Santos, Bruna Souza dos (2015)
In recent years there has been a growth of industrial activities that caused significant impacts to natural resources, and concerns about the environment in general are of particular importance. In this context, the textile industry considered an important activity responsible for part of that development is characterized as liquid effluent generating widely polluter due to the large volume of water needed in this production process. Taking into account the conventional methods and also the difficulties in treating textile effluents, the electrolytic process known as eletrofloculation constitutes an important possibility. This process involves the destabilization of the emulsified pollutants, or suspension in aqueous medium. Thus the aim of this study was to implement a hybrid treatment system used in removing the blue reactive dye 5G of a synthetic textile effluent by eletrofloculation associated with adding natural coagulant the basis of Moringa Oleifera Lam, in order to enhance the level treatment would be achieved with the techniques used alone initially worked up exclusively with eletrofloculation to remove the dye. The variables analyzed were: ddp (potential difference applied), time and pH. Whereas the 95% confidence interval only the quadratic term of the linear term DDP and pH were significant. The removal of color values for the tests ranged from 64.38 to 90.87% and validating an average removal of 89.01%, very close values predicted by the model. Following was carried out to optimize the conditions for obtaining the aqueous extract of Moringa oleifera. Salinity and extraction time: The following conditions were evaluated. The concentration of the coagulant obtained in synthetic turbid water was also one of the factors studied. The best conditions for the aqueous extract of Moringa oleifera were 20 seconds of ultrasound in agitation, and solution of 20% sodium chloride. To enhance the level of treatment the two techniques (eletrofloculation and natural coagulant Moringa oleifera the base), were initially tested in batch and following streaming. The batch tests were divided into two parts, the first CCRD evaluated the intensity of electric current (I), the time eletrofloculation and concentration of the coagulant (MO), which obtained a color removal of 91 to 77.27% 33%. But no term was significant, but time showed less effect. Thus, a new planning was done, the second CCRD, setting the time at a minimum, in addition to the R and MO tracks that were also reduced. There was thus obtained a removal color for testing 13.45 to 80.8%, and validating an average removal of 86.56%. For the continuous form, the variables studied were the intensity of electric current (I), the coagulant concentration (MO) and hydraulic retention time (HRT). Among them only HRT was not significant. The color removal ranged from 8.46 % to 90.25%. In these assays were also performed the analysis of the residual iron concentrations, and the values obtained ranged from 3.70 mg L- 1 to 9.03 mg.L-1, were below the maximum value allowable by law (15 mg.L-1). To maximize the removal of color and minimize the residual concentration of iron, the desirability function STATISTICA ™ software was used and under these conditions only I and MO were significant. From the validation was observed removing trend predicted by the model. Obtained was a color removal for the validation of 71.38 % and an average concentration of 5.2237 mg.L-1 of residual iron, but with a far from the expected error (32.85%).